The effect of corporate governance mechanisms on corporate performance in Malaysia during COVID-19 pandemic / Muhammad Hafiz Muhamud Fuzi ... [et al.] - Muhamud Fuzi, Muhammad Hafiz; Mohd Suffian, Mohd Taufik; Kabir, Mohammad Rokibul; Omar, Nor Bahiyah (UiTM Press, 2024)
This research aimed to explore how corporate governance mechanisms affect the performance of firms in Malaysia. The study focused on 135 companies listed in the Bursa Malaysia Main Market within the consumer sector, covering the years 2020 and 2021. The dependent variable in this investigation was firm performance, while the independent variables were corporate governance mechanisms, specifically board size, board independence, board meetings, and board expertise. Amidst the COVID-19 pandemic, all aspects of companies, including corporate performance, governance structure, dividend, liquidity, and leverage level, were impacted. However, there remains a lack of a comprehensive understanding of the specific effects of the pandemic on these factors. Therefore, this study sought to shed light on how corporate governance mechanisms influenced corporate performance during the COVID-19 pandemic in Malaysia. The analysis revealed varied outcomes concerning the impact of board size, board independence, and board meetings on corporate performance; in which only board meetings were significantly related to corporate performance. This research contributes to the existing but limited body of literature by providing empirical evidence of the relationship between corporate governance mechanisms and corporate performance during the COVID-19 pandemic in Malaysia.